Pengaruh Penyajian Dan Aksesibilitas Laporan Keuangan Daerah Terhadap Akuntabilitas Pengelolaan Keuangan Daerah - Eva marin sambo; anim wiyana (Insan Cita Bongaya Research Journal, 2022)
This study aims to determine whether the presentation and accessibility of regional financial reports affect the accountability of regional financial management at the Regional People's Representative Council of Gowa Regency. Data collection uses primary data obtained from 45 members of the DPRD Gowa Regency using a saturated sampling technique. The population of this study were 45 members of the Regional People's Representative Council of Gowa Regency. The results of the questionnaire data have been tested by instruments, classical assumptions and methods of data analysis using multiple regression techniques. The results showed that all hypotheses were accepted because the presentation and accessibility of Regional Financial Statements had a significant positive effect on the Accountability of Regional Financial Management at the Regional Representative Council of Gowa Regency.